Microstructure homogenization of laser powder bed fusion support-free low angle IN718 walls through heat treatment - Minsol Park; Mudit Kesharwani; Mohammad Attarian Shandiz; Mathieu Brochu (Additive Manufacturing Letters)
This study investigates the effectiveness of heat treatment (HT) to homogenize the microstructural and mechanical asymmetry between the bulk and the downskin regions of support-free IN718 walls fabricated at angles of 30°, 20°, 15°, and 10° In the as-built condition, the microhardness ranged from 340 ± 5 HV to 351 ± 4 HV for the bulk and from 315 ± 4 HV to 323 ± 10 HV for the downskin region, resulting in a maximum difference range of 35 HV. The HT eliminated this difference where microhardness values of 482 ± 3 HV in the bulk and 478 ± 4 HV in the downskin were measured. The HT induced γ″ precipitation with volume fraction and mean precipitate size in the bulk of 16.6 % and 24.7 ± 7.3 nm. These values are statistically comparable to those in the downskin: 15.8 % and 26.5 ± 7.9 nm. The similarity in the γ″ characteristics explains the recovery of the mismatch in hardness as γ″ contributes approximately 85 % of the strengthening in the HT condition.